2021
DOI: 10.1038/s41598-021-83198-w
|View full text |Cite
|
Sign up to set email alerts
|

Defining the epitope of a blood–brain barrier crossing single domain antibody specific for the type 1 insulin-like growth factor receptor

Abstract: Ligand-activated signaling through the type 1 insulin-like growth factor receptor (IGF1R) is implicated in many physiological processes ranging from normal human growth to cancer proliferation and metastasis. IGF1R has also emerged as a target for receptor-mediated transcytosis, a transport phenomenon that can be exploited to shuttle biotherapeutics across the blood–brain barrier (BBB). We employed differential hydrogen–deuterium exchange mass spectrometry (HDX-MS) and nuclear magnetic resonance (NMR) to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…IGF1R3, IGF1R4, and IGF1R5 sdAbs (V H H format) showed high‐affinity binding to human‐IGF1R with K D s of 1.3, 0.3, and 0.6 nM, respectively (Figure 1). The binding epitope of IGF1R5 sdAb on IGF1R has recently been characterized in detail 48 . Neither of the IGF1R V H Hs bound the insulin receptor ectodomain (data not shown).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…IGF1R3, IGF1R4, and IGF1R5 sdAbs (V H H format) showed high‐affinity binding to human‐IGF1R with K D s of 1.3, 0.3, and 0.6 nM, respectively (Figure 1). The binding epitope of IGF1R5 sdAb on IGF1R has recently been characterized in detail 48 . Neither of the IGF1R V H Hs bound the insulin receptor ectodomain (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…The binding epitope of IGF1R5 sdAb on IGF1R has recently been characterized in detail. 48 Neither of the IGF1R V H Hs bound the insulin receptor ectodomain (data not shown).…”
mentioning
confidence: 90%
“…Thus, IGFs can reach the CSF and specific regions of the brain. IGF1R has also emerged as a target to promote receptormediated transcytosis [100]. VHH-IR5, a nanobody targeting the type 1 insulin-like growth factor receptor 5 (IGF1R), does not appear to interfere with IGF1R kinase activity and its interactions with the endogenous ligand IGF-1.…”
Section: Receptor-mediated Transcytosismentioning
confidence: 99%
“…VHH-IR5, a nanobody targeting the type 1 insulin-like growth factor receptor 5 (IGF1R), does not appear to interfere with IGF1R kinase activity and its interactions with the endogenous ligand IGF-1. VHH-IR5 targets with high affinity a linear epitope at the α-helix in the C-terminal segment (α-CT) of IGF1R, sharing the binding site of IGF-1 in an independent and non-competitive manner [100,101], suggesting a potential role of the α-CT in VHH-IR5 transcytosis across the BBB.…”
Section: Receptor-mediated Transcytosismentioning
confidence: 99%
“…The use of VHHs for BBB transcytosis and target engagement is promising. Specifically, Stanimirovic et al identified an insulin-like growth factor 1 receptor binding VHH which crosses the BBB by receptor mediated transcytosis [30, 31]. Danis et al identified and optimized VHHs to mitigate brain accumulation of pathological tau in a tauopathy mouse model [32].…”
Section: Introductionmentioning
confidence: 99%